Hydrogels loaded with cell-derived nanovesicles for skin repair - Teo, Chun Keong (Nanyang Technological University, 2021)
With the increasing ubiquity of chronic diseases, there is motivation to discover novel bioactive therapy to alleviate debilitating complications experienced by patients with chronic wounds. Various pathophysiological factors can cause anomalies that constantly disrupt the natural reparative healing process lowers the patient’s life quality substantially, both physically and emotionally. Over the past decade, stem cells are widely considered to be promising candidates for therapeutic agents due to their properties. While they have excellent self-renewal and replicating properties, the sophisticated and low yield procedure limit the ability to extract a sizeable amount to be used in a controlled drug delivery application. Cell-derived nanovesicles (CDNs) were discovered and developed as a solution that mimics the paracrine signaling function in their counterpart while attaining exceptional potential to be mass-produced. This project aims to explore and evaluate the interaction and release effects of CDNs from chitosan-based hydrogel and the efficacies of its applications in bioactive therapy. Biocompatibility and bioactivity response of the epithelial cells from CDN release and its interactions with the chitosan hydrogel was examined by employing various cell studying techniques. CDNs of various cell lines, such as U937, HUVEC, OLG, and ADSC, were fabricated and individually loaded homogeneously in synthesized chitosan hydrogel through a physical crosslinking mechanism using Chitosan and gelling agents of β -Glycerophosphate(βGP) and Sodium Hydrogen Carbonate (SHC). We concluded that the CH hydrogel does not slow down or prevent cell viability and proliferation when applied on endothelial cells, while the free Cy5 attached to the U937 CDN does not have any observable effects on the proliferation of the endothelial cells. This implied that the CH hydrogel does not have any detrimental/toxic effects when utilized, making it an ideal Drug Delivery System (DDS). We expanded the study to further understand the effects of the introduction of CDNs from different system and origin source. U937, HUVEC, ADSC and OLG -CDNs showed very promising potential and capabilities to be used as CDN candidates with ADSC and OLG -CDNs OLG show promises of being a better candidate due to the similar effectiveness albeit at a lower concentration used. Additionally, this opens the opportunity for further research regarding the use of cross-tissue or -species CDNs, which allows the possibility of an abundance of inexpensive variety of products catering for wound care under diabetes. Fluorescence was observed across all the skin-cartilage interfaces of the pig ear tissues treated with Cy5 labelled U937 CDNs across different optical magnifications. This is indicative of the presence of the cellular uptake mechanism as well as tissue retention of CDNs taking place. A continuation of the current studies will help to further understand various potential CDN candidates, paving the development of a translational product to enhance wound healing. A better understanding of the scalability and regenerative capabilities of CDN based technologies is also instrumental in discovering a safer and more effective therapeutic alternative that can potentially revolutionize wound care management.